ECG Changes and Their Prognostic Impact in Patients With Takotsubo Syndrome - Piackova1, Edita; Kaufmann, Christoph C.; Weihs, Valerie; El-Razek, Abd; Geppert, Alexander; Nürnberg, Michael; Wessely, Emil; Smetana, Peter; Weiss, Thomas; Huber, Kurt (Cardiology and Cardiovascular Medicine, 2019)
Aim: Within this study, we investigated ECG changes in acute patients diagnosed with Tako Tsubo syndrome (TTS) and report on the prognostic impact of the respective ECG patterns. Methods and Results: This single-center study included 101 consecutive patients diagnosed with TTS between 2006 and 2017. Upon 12-lead admission ECG, 59 patients had ST-segment elevation (58%, STEMI), 9 patients had only ST-segment depression (9%, NSTEMI) and 27 T-wave inversion (27%, NSTEMI). Patients who were admitted to the hospital 12 hours after symptom onset were more likely to present with Twave inversion on ECG (T-inversion 47% vs. STelevation 23% ST, p= 0,05). T-wave inversion was also associated with significantly higher values of NT-pro- BNP (p=0,024), while high-sensitive cardiac troponin I (hs-CTnI) and creatine kinase (CK) were comparable between the groups. There was no difference in ECG changes among the different types of TTS (apical, midventricular, apical-midventricular and basal type). In a second step, patients with ST-segment elevation were divided into three groups based on the pattern of STsegment elevation: Group A (concave type, n=35), group B (straight type, n=8) and group C (convex type, n=10), respectively. Straight type ST-segment elevation was associated with a higher incidence of in-hospital MACE (p = 0,002), while patients with convex type STelevation were hospitalized for a longer time (p= 0,010). There was no difference in three-year all-cause mortality based on repolarization abnormalities ((χ2(2) = 0,839, p=0,657) or the pattern of ST-elevation ((χ2(2) = 0,501, p=0,778). Conclusion: The present study describes typical ECG changes in TTS and highlights their impact on cardiac biomarkers and clinical outcomes. There was no prognostic difference between ST-elevation, STdepression or T-wave inversion at admission ECG, however straight-type pattern of ST-segment elevat